The EU, China, and the future of climate finance - Niall Duggan; Kim Vender; Jörn-Carsten Gottwald (Asia Europe Journal, 2025)
Relations between the European Union (EU) and the People's Republic of China (China) face substantial strains. Cooperation in the fight against global warming seems to be one of the few areas where a strategic partnership might still be possible. Within the field of climate change governance, the issue of climate finance has gained substantial significance and was at the core of COP29. Here, important developments indicate a complex scenario for future collaboration: the EU's hopes to preserve climate change as an “island of opportunity” for collaboration meet a Chinese revision of climate policy that seeks to raise it to a key foreign policy issue—thus linking it with core interests. At the technical level, despite several MoUs and declarations of intended cooperation, in climate finance, China and the EU have not agreed on a Chinese contribution to the Loss and Damage Fund at COP28. Finally, regarding the New Collective Quantified Goal on Finance, the EU and China are aligned on the importance of an updated goal but differ on how climate finance obligations should be structured. In the paper, we explore the current state of affairs in EU-China cooperation regarding climate finance (governance). We highlight the recent revision of China's foreign policy approach and trace the positioning of both sides toward and at COP29. The paper identifies where the EU and China are diverging and converging in their approaches to climate finance and indicates future policy options.
Keywords: 300